A clinical study on the usefulness of autologous plasma filler in the treatment of nasolabial fold wrinkles. (3rd April 2017) - Choi, Young-Jun; Kim, Han-Saem; Min, Joon Hong; Nam, Jae-Hui; Lee, Ga-Young; Kim, Won-Serk
ABSTRACT: Background : Recently, the efficacy of autologous plasma filler for the reduction of facial wrinkles has been demonstrated.Objective : The aim of our study is to validate the efficacy and safety of autologous plasma filler in treating nasolabial fold wrinkles.Material and methods : Twenty Korean patients with moderate-to-severe nasolabial fold wrinkles were enrolled. The patients were treated with one session of autologous plasma filler. The wrinkle improvement effects were evaluated at 1-week, 4-week, 8-week, and 12-week after the treatment. Three assessment methods were applied. First, two independent dermatologists assessed cosmetic results using a 5-point wrinkle assessment scale. Second, global aesthetic improvement score was used for assessment of the final cosmetic results. Third, patient satisfaction was surveyed. Also, the adverse effects associated to treatment were observed.Results : Mean age of the patients was 44.5 years. The average 5-point wrinkle assessment scale score was significantly improved at 1, 4, 8, and 12 weeks after treatment, comparing to before treatment ( p < 0.01). The patients' average global aesthetic improvement score also indicated better cosmetic outcomes.Conclusion : The clinical improvement with sufficient patients' satisfaction and no significant adverse events demonstrated that novel autologous plasma filler could be considered as efficient and safety treatment option for nasolabial fold wrinkles.